2009
DOI: 10.1002/lsm.20799
|View full text |Cite
|
Sign up to set email alerts
|

In vitro large diameter bowel anastomosis using a temperature controlled laser tissue soldering system and albumin stent

Abstract: This report describes the in vitro LTB anastomosis of a large diameter cylindrical organ. The immediate bond strength, as estimated by burst pressure measurements, was double compared to sutured anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The produced heat is essential to bond tissue to solders or chitosan adhesives. Unfortunately, the tissue damage associated with the exothermal absorption of the dye can be detrimental because tissue temperature often exceeds 70°C [16]. At this temperature, albumin and collagen molecules denature and crosslink together.…”
Section: Introductionmentioning
confidence: 99%
“…The produced heat is essential to bond tissue to solders or chitosan adhesives. Unfortunately, the tissue damage associated with the exothermal absorption of the dye can be detrimental because tissue temperature often exceeds 70°C [16]. At this temperature, albumin and collagen molecules denature and crosslink together.…”
Section: Introductionmentioning
confidence: 99%
“…This real-time system enables the surgeon to halt welding when the corneal surface temperature exceeds 65°C, which was previously found to be the upper limit of the surface temperature in which there is no denaturating photothermal injury to the irradiated cornea [20]. Fibers made of polycrystalline halides are used because they are highly transparent in the mid-infrared range, unlike the standard optical fibers of a Nd:YAG laser [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Oz et al [11], DeCoste et al [12], and Bass et al [13] have shown that ICG is an effective chromophore for this purpose. LTS has been successfully utilized in anastomoses of various tissues including the gastrointestinal tract [14,15], blood vessels [16,17], cartilage [18], skin [19,20], bladder [21], and urethra [22], predominantly in ex vivo and in vivo animal studies.…”
Section: Introductionmentioning
confidence: 99%